Nonlinear topological mechanics - Tjoa, Erico (2018)
In this project I studied non‐linear topological mechanical systems. Similar to electronic system, topological classification methods, such as winding number, can be used to characterize mechanical system. Mechanical spring system with certain non‐linearity can be engineered to exhibit self‐induced topological transition. Self‐induced topological transition is studied for SSH system by Andrea Alu et al. A more natural non‐linearity of spring mass system is shown to not exhibit topological transition. Further, I also studied nonlinear Haldane model, coupled pendulum and learnt to create GUI program in order to visualize and solve problems on the go.